Upaya peningkatan mobilitas fisik pada pasien stroke nonhemoragik di rsud dr. Soehadi Prijonegoro - Dodya Pradana, Mahardika, Okti Sri Purwanti, S.Kep, Ns, M.Kep .,Ns SP.Kep. MB (2016)
The problem that frequently appear in stroke patient is impaired motion. Patient experiencing interruptions or difficultes when running because experienced disturbances on muscle strength and body balance. It is important to do mobilization exercise or rehabilitation to improve the muscle strength, rehabilitation is important to improve the neurologis function and prevent the contractures or muscle stiffness which can be done by physical therapy and other techniques. To give an overview of physical mobility improvement effort in the patient with non-hemorrhagic stroke and to prevent the muscle rigidity in the patient with stroke. Method used was a descriptive with case study approach toward patient with stroke in the inpatient installation room of Sakura at dr. Soehadi Prijonegoro conducted from 28th to 30th of March, 2016 including five nursing processes start from the assessment, diagnosis, intervention, implementation and evaluation. The data was obtained from the medical records, observation, interview, physical examination and journals and books documentation. Patient indicated an improvement in the physical mobility after the treatment. The physical improvement due to the effect of Range Of Motion (ROM) treatment and control bearing to improve the physical mobility. A nursing problem of physical mobility disorder has been solved partially, therefore it requires for further treatment or mobilization exercises. Not all nursing problems have been done, thus require for more nursing treatment.